2003
DOI: 10.1186/gb-2003-4-8-r47
|View full text |Cite
|
Sign up to set email alerts
|

Recent segmental and gene duplications in the mouse genome

Abstract: Recent segmental and gene duplications in the mouse genome Our results provide an initial analysis of the recently duplicated sequence and gene content of the mouse genome. Many of these duplicated loci, as well as regions identified to be involved in potential sequence misassignment errors, will require further mapping and sequencing to achieve accuracy. A Genome Browser database was set up to display the identified duplication content presented in this work. This data will also be relevant to the growing num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
27
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…We therefore searched for additional chromosomal aberrations besides those identified as the main aberration in the 22q11 region and the ␤-globin locus on chromosome 11p15, respectively. We observed a large number of signals that correspond in their chromosomal coordinates to previously reported CNPs (3,17). In addition to these putative known CNPs, in our samples we also found evidence for novel CNPs.…”
Section: Detection Of Increases In Copy Numbersupporting
confidence: 52%
See 2 more Smart Citations
“…We therefore searched for additional chromosomal aberrations besides those identified as the main aberration in the 22q11 region and the ␤-globin locus on chromosome 11p15, respectively. We observed a large number of signals that correspond in their chromosomal coordinates to previously reported CNPs (3,17). In addition to these putative known CNPs, in our samples we also found evidence for novel CNPs.…”
Section: Detection Of Increases In Copy Numbersupporting
confidence: 52%
“…With a sequence identity cutoff of 80%, this led to the identification of regions with high repeat density (Fig. 2), which largely correspond to previously described segmental duplications [see, for example, http:͞͞projects.tcag.ca͞humandup (17)]. Some of these regions coincide well with the LCR regions in 22q, including those relevant for diseases resulting from aberrations in 22q11 (Fig.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…We found that 10% of BACs showing loss and 1% of BACs showing gain were associated with segmental duplications 4,5 (Supplementary Table 2 online); such association was found in only 3% of randomly selected BACs. The frequent association (P o 0.0005) of segmental duplication with BACs showing loss suggests that a recombination-mediated sequence-deletion mechanism, similar to that found in some human genomic disorders 6 , could lead to some of these copy-number variations.…”
mentioning
confidence: 94%
“…Fluorescent in situ hybridization (FISH) and in silico studies have shown that at least 5% of the human genome is composed of these SDs, often containing complete or partial copies of genes (Bailey et al 2001(Bailey et al , 2002. They have emerged during the past 35 million years of evolution of our taxa (Bailey et al 2001(Bailey et al , 2002Eichler 2001;Lander et al 2001;Venter et al 2001;Cheung et al 2003). These repeated sequences tend to be located preferentially in pericentromeric and subtelomeric regions (Bailey et al 2001;Cheung et al 2003).…”
mentioning
confidence: 99%